2011
DOI: 10.11645/5.1.1513
|View full text |Cite
|
Sign up to set email alerts
|

Faculty attitudes, perceptions and experiences of information literacy:

Abstract: This Canadian-based survey research study investigates the information literacy (IL) instruction practices, attitudes and knowledge of university faculty. Findings are based on results from an online survey of all full-time faculty at York University. The value of this paper lies, firstly, in its contribution to a field of enquiry where a research deficit has been identified. Second, it contributes to IL research and practice by both synthesizing and corroborating some of the findings of earlier studies of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 24 publications
6
83
0
1
Order By: Relevance
“…In comparison, response rates for other surveys of faculty reported recently in the literature ranged from 15% to 52% (Bury 2011;National Study;Shannon and Bradshaw 2002;Cook, et al, 2000;Park and Denson 2009;Briggs and Pehrsson 2010).…”
Section: Response Ratementioning
confidence: 79%
See 2 more Smart Citations
“…In comparison, response rates for other surveys of faculty reported recently in the literature ranged from 15% to 52% (Bury 2011;National Study;Shannon and Bradshaw 2002;Cook, et al, 2000;Park and Denson 2009;Briggs and Pehrsson 2010).…”
Section: Response Ratementioning
confidence: 79%
“…There are many reports of collaborations on teaching information literacy competencies between faculty in the disciplines and others on campus, particularly librarians (Bury 2011;Johnson, Whitfield, and Grohe 2011;Allner 2010;Dobozy and Gorss 2010;Kobzina 2010;Barratt 2009;Dugan 2008;Caravello 2008;Madray 2008;Floyd, Colvin, and Bodur 2008;Elrod and Somerville 2007). Because of the extensive work done to operationalize and promote information literacy by organizations such as the Association of College and Research Libraries, academic librarians teach information literacy competencies through credit-bearing courses, guest-lectures in courses or co-curricular learning activities, participating as "embedded" librarians on problem-based learning or course project teams, and consulting with students and faculty individually.…”
Section: Responsibility For Teaching Information Literacy Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For their part, faculty members are often dissatisfied with students' information literacy abilities, though they may not always agree with librarians about the best ways to improve those abilities (Bury, 2011;DaCosta, 2010;Dubicki, 2013;Saunders, 2012). Although some librarians have found the attitudes and values of teaching faculty "barriers" to effective information literacy program implementation (Saunders, 2009), a wealth of case studies have reported successful collaborations between librarians and faculty to improve student information literacy learning (Bluemle et al, 2013;Johnson et al, 2003;Ostrow, 2010;Winterman et al, 2011; for a thorough review of faculty-librarian collaborations for composition courses between 1998-2007, see Mounce, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One such study by Cope and Sanabria (2014) implies that the absence of librarian involvement in course teaching may be because faculty members conceptualize information literacy as a part of the discipline teaching. In the past 10 years six critical studies (Bury, 2011(Bury, , 2016Cope and Sanabria, 2014;Dacosta, 2010;Dubicki, 2013) have investigated faculty conceptions of information literacy, and have built on Bruce's "Seven Faces of Information Literacy" (1997) and Boon et al's (2007) seminal research of English faculty perceptions of information literacy, to offer some insight into the information literacy pedagogy of teaching faculty.In four of these studies (Bury, 2011;Dacosta, 2010;Dubicki, 2013;Saunders, 2012) the researchers have presented an understanding of information literacy as one that parallels what faculty perceive as necessary information literacy standards and competencies in their disciplines. Although Saunders (2012) suggests that while many members of faculty perceived information literacy instruction as falling outside of their responsibility, this was not corroborated in these other studies, as all four studies indicate that in addition to recognizing and valuing information literacy standards, faculty consistently taught and evaluated some of the skills through their instruction, assignments and course projects.…”
mentioning
confidence: 99%